2021
DOI: 10.1007/s00787-021-01828-0
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders among adults formerly in out-of-home care: a systematic review and meta-analysis of longitudinal studies

Abstract: While children and adolescents placed in child welfare or juvenile justice out-of-home care show higher prevalence rates of mental disorders compared to the general population, it remains unclear whether this pattern persists into adulthood. A quantitative synthesis of existing studies is lacking. The aim of this meta-analysis was to estimate the prevalence rates for mental disorders among adults with a foster or residential child welfare or juvenile justice care history, comparing them where possible to rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 95 publications
1
30
1
Order By: Relevance
“…Our results are consistent with the findings of previous meta-analyses of mental disorders among adolescents in the juvenile justice system [13] and adolescents placed by the child welfare system [11], and these rates are far higher compared to a pooled prevalence rate (13%) for any mental disorder among children and adolescents in the general population [12]. In the present study, the prevalence rate of 86% for any mental disorder among the total sample in adulthood (child welfare: 83%; juvenile justice: 94%) is higher than in a recent meta-analysis of mental disorders in adults formerly placed in out-of-home care by child welfare or juvenile justice authorities [35], and also far higher than a pooled prevalence rate of 18% for any mental disorder in the general adult population [68]. The high prevalence rates found in the present study may be due to the inclusion of both child welfare and juvenile justice youths.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Our results are consistent with the findings of previous meta-analyses of mental disorders among adolescents in the juvenile justice system [13] and adolescents placed by the child welfare system [11], and these rates are far higher compared to a pooled prevalence rate (13%) for any mental disorder among children and adolescents in the general population [12]. In the present study, the prevalence rate of 86% for any mental disorder among the total sample in adulthood (child welfare: 83%; juvenile justice: 94%) is higher than in a recent meta-analysis of mental disorders in adults formerly placed in out-of-home care by child welfare or juvenile justice authorities [35], and also far higher than a pooled prevalence rate of 18% for any mental disorder in the general adult population [68]. The high prevalence rates found in the present study may be due to the inclusion of both child welfare and juvenile justice youths.…”
Section: Discussioncontrasting
confidence: 83%
“…Previous studies have revealed that older youths in foster care show disproportionally high rates of lifetime and past-year psychiatric disorders [e.g., 34], and adults with a history of child welfare out-of-home care showed a prevalence rate of 30% for any mental disorder [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strength of the current study is the long follow-up interval of 10 years. This is noteworthy given that young-adult care leavers (i.e., juveniles who left residential care or juvenile-justice institutions) are often difficult to locate, since many live in rather unstable and changing circumstances ( 65 ) or suffer from severe mental-health disorders ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the care experience, especially the type of care placement, in mitigating or increasing mental health problems is not yet fully understood [8]. Development of mental health problems in childhood and adolescence can continue into later life [9], although there is also evidence of stabilization in positive behavioral adjustment [10]. Mental health problems are also associated with a range of other adverse outcomes, notably lower levels of educational attainment and engagement [11,12].…”
Section: Introductionmentioning
confidence: 99%